A `spirituality of risk' for christian witness in South Africa - Ackermann, Denise M. (International Review of Mission, 1994)
Seeks a viable, vibrant spirituality for mission in South Africa today. The South African context; Spirituality; Spirituality of risk; Mozambique as an example of spirituality of risk.
free
Keywords: CHRISTIAN missions; SOUTH Africa; SPIRITUALITY